Chemistry's metaphysics - Seifert, Vanessa A. (Cambridge elements. Elements in metaphysics, 2023)
The place of chemistry in the metaphysics of science may be viewed as peripheral compared to physics and biology. However, a metaphysics of science that disregards chemistry would be incomplete and ill-informed. This Element establishes this claim by showing how key metaphysical issues are informed by drawing on chemistry. Five metaphysical topics are investigated: natural kinds, scientific realism, reduction, laws and causation. These topics are spelled out from the perspective of ten chemical case studies, each of which illuminates the novel ways that metaphysics of science can be informed by chemistry. This title is also available as Open Access on Cambridge Core.